Understanding Consumer’s Responses to Enterprise’s Ethical Behaviors: An Investigation in China - Deng, Xinming (Journal of business ethics, 2012)
The response of consumers to a firm’s ethical behavior and the underlying factors influencing/forming each consumer’s response outcome is analyzed in this article based on information obtained through interviews. The results indicate that, in the Chinese context, the responding outcome can be boiled down to five types, namely, resistance, questioning, indifference, praise, and support. Additionally, consumers’ responses were mainly influenced by the specific consumer’s ethical consciousness, ethical cognitive effort, perception of ethical justice, motivation judgment, institutional rationality, and corporate social responsibility–corporate ability (CSR–CA) belief. Based on these results, a generalized framework of consumer’s ethical responses is developed which provides a number of insightful suggestions upon how to motivate a consumer’s support of a firm’s ethical behavior and to transfer this kind of support into truly positive purchasing behavior.